Analisis Determinan Impor Barang Konsumsi di Indonesia: Pendekatan Error Correction Model - Hardi, Bima; Hawihanus, Hawihanus; Riyadi, Slamet (Medan Resource Center, 2023)
This study was conducted to look at the effects of currency reserves, inflation, and dollar exchange rates on consumer goods imports in Indonesia using the error correction model (ECM) method. The result of the short-term regression was D(Y) = -75,75310 + 4,21E-08 D(X1) – 31,52554 D (X2) + 0,314495 D(X3) – 0,561151 ECT, and the result of the long-term regression was Y = 1489,170 + 6,30E-09 X1 – 15,06641 X2 + 0,355049 X3. Reserves have (X1) a partial short- and long-term foreign no impact on economic growth in Indonesia. Inflation (X2) in the short term and in the long term has no effect on Indonesian gross domestic product (GDP). Exchange rate (X3) has no short-term or long-term effect on Indonesia’s GDP. The result of the simultaneous test (test F) of the short-term prob values are 0,011006 < 0,05 and Fcalung (4,128184) > Ftable (2,98), and the long-term prob value is 0,000010 < 0.05 and Fcalung value (14,41331) > Ftable (2,98).